Penerapan Model Pembelajaran Reflektif pada Pembelajaran Biologi terhadap Hasil Belajar Siswa Kelas X SMA Negeri Colomadu Tahun Pelajaran 2012/2013 - Abdi Prasetyo; Slamet Santosa; Marjono Marjono (Universitas Sebelas Maret, 2014)
The purpose of the research is to know the influence application of Refelective Learning model toward biology learning achievement of tenth degree students at SMA Negeri Colomadu in academic year 2012/ 2013. This research was Quasi Experiment research which used Posttest Nonequivalent Control Group Design. This research applyed Reflective Learning model in experimental group and Direct Instruction Learning model in control group. Population’s research is the entire class tenth at SMA Negeri Colomadu in academic year 2012/2013. Sampling technique used Cluster Sampling, result has chosen tenth 5 as experiment group and tenth 4 as control group. Data was collected using document, observation sheet, and multiple choice test. The data were analyzed by t-test. Result of the research in biology learning achievement between experiment and control group have real differents in cognitive, psychomotor, and affective domain. The conclusion that application of Refelective Learning model has taken good effect toward biology learning achievement of tenth degree students at SMA Negeri Colomadu in academic year 2012/2013. Key Words: Refelective Learning Model, Learning Achievement